Neurokriminologi Psikopat: Determinisme Genetik atau Deprivasi Lingkungan? - Zul Khaidir Kadir (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Psychopathic disorders are often reduced to medical issues related to structural brain abnormalities or genetic predisposition, while the contribution of the social environment to their development is often overlooked. This article aims to evaluate claims of genetic determinism in neurocriminology and analyze the role of environmental deprivation as a factor shaping the nervous system relevant to psychopathy. The research method used is qualitative research with a conceptual approach. The results indicate that claims of genetic determinism lack sufficient explanatory power when separated from environmental dynamics. Findings regarding the MAOA-L gene and abnormalities in the amygdala or prefrontal cortex are indeed correlated with antisocial tendencies, but this relationship is contingent and nonlinear. Psychopathy, in this configuration, is the result of the interaction between neurobiological systems and cumulative social experiences. Therefore, an interactional model is needed not only to conceptually understand the etiology of psychopathy but also as a basis for formulating more accurate and ethical forensic assessments, rehabilitation policies, and criminal interventions.